The effect of light and outdoor activity in natural lighting on the progression of myopia in children - Sánchez-Tocino, H.; Villanueva Gómez, A.; Gordon Bolaños, C.; Alonso Alonso, I.; Vallelado Alvarez, A.; García Zamora, M.; Francés Caballero, E.; Marcos-Fernández, M.; Schellini, S. [UNESP]; Galindo-Ferreiro, A. (Elsevier, 2019)
Purpose: To investigate potential risk factors for the progression of myopia. Methods: Prospective study. Myopic progression was evaluated by cycloplegic autorefraction and axial length (AL) every 6 months in children 6 to 15 years old. Univariate analysis and multiple logistic regression were applied. Results: Around 82 children with median age of 10.3 ± 2.3 years. Myopia progressed by −0.816 ± 0.6 D over 18 months. Increased myopic spherical equivalent refraction (SER) was correlated with increase in AL (P < 0.001). Univariate analysis found SER to be significantly associated with: age, especially between 6 and 9.4 years old (P = 0.001), parental myopia (P = 0.028), and less time spent outdoors (P = 0.009). There was a significantly greater increase in SER during months with the least daylight hours (P < 0.001). Conclusion: Outdoor activities and daylight have a protective effect against increased AL and progression of myopia. Younger children with significant myopia should be monitored closely, especially those around 6 years old with myopic parents.
L'effet de la lumière et le temps passé dehors, à la lumière naturelle, dans la progression de la myopie chez les enfants
Keywords: Children; Myopia; Outdoor activities; Progression; Risk factors